Sarcopenia is a predictive factor for intestinal resection in admitted patients with Crohn’s disease - Bamba, Shigeki (PLoS One, 2017)
The relationship between skeletal muscle volume and the prognosis of patients with inflammatory bowel disease (IBD) remains undetermined. We conducted a retrospective study of 72 IBD patients who were admitted to the hospital due to disease exacerbation. We enrolled IBD patients who had undergone abdominal computed tomography and assessed the nutritional indices, such as the Onodera’s prognostic nutritional index (O-PNI) and the controlling nutritional status (CONUT) index. The L3 skeletal muscle index (SMI), which is the ratio of the cross-sectional area of skeletal muscles at the level of the third lumbar (L3) vertebra to the height squared, was used to identify sarcopenia. Sarcopenia, defined as a low SMI, was observed in 42% of all IBD patients (37% with Crohn’s disease (CD) and 48% with ulcerative colitis (UC)). In UC patients, the O-PNI and CONUT values, height, and albumin levels were significantly lower than in CD patients. The SMI strongly correlated with sex, body weight, albumin level, and O-PNI in IBD patients. Multivariate analysis using the Cox regression model demonstrated that the presence of sarcopenia (P = 0.015) and disease type (CD or UC) (P = 0.007) were significant factors predicting intestinal resection. The cumulative operation-free survival rate was significantly lower for sarcopenic patients than in all IBD patients (P = 0.003) and a stratified analysis of CD patients (P = 0.001) using the Kaplan–Meier method and log-rank test. The L3 skeletal muscle area is a prognostic factor for intestinal resection in patients with CD.